Heat-resistant Pb(ii)-based X-ray scintillating metal–organic frameworks for sensitive dosage detection via an aggregation-induced luminescent chromophore. Issue 22 (27th May 2020) - Lu, Jian; Wang, Shuai-Hua; Li, Yan; Wang, Wen-Fei; Sun, Cai; Li, Pei-Xin; Zheng, Fa-Kun; Guo, Guo-Cong
Abstract : Unusual X-aggregation induced luminescent chromophores in heat-resistant Pb(ii )-based metal–organic frameworks facilitate excellent scintillation for X-ray dosage detection. Abstract : The synergy of unusual X-aggregation induced luminescent chromophores and heavy Pb(ii ) ions has facilitated excellent X-ray scintillation of two structurally similar Pb-SMOFs, which are heat-resistant due to solvent-free lattices. Owing to their higher Pb(ii ) contents, Pb-SMOFs with larger X-ray absorption coefficients are more sensitive for X-ray dosage detection than powdered CsPbBr3 .